Analisis Sumber Daya Koping dan Perceived Stress Mahasiswa Menggunakan Brief Cope dan Perceived Stress Scale: Kajian Kuantitatif - Efvelin Barus; Akhmad Muzakki; Roikhatul Jannah ((JPAP) Jurnal Praktisi Administrasi Pendidikan, 2026)
This study aims to analyze coping resources and perceived stress levels among students at the Bakti Negara Islamic Institute in Tegal and to examine the relationship between the two variables. The research method used a correlational quantitative approach with a sample of 38 students selected through convenience sampling. The instruments used were the Brief Cope Scale and the Perceived Stress Scale (PSS). The results showed that the majority of students were in the moderate coping category (68.4%) and moderate stress category (57.9%). The correlation test yielded a value of r = -0.383; p = 0.018, which means that there is a significant negative relationship between coping resources and perceived stress. The better the students' coping strategies, the lower their perceived stress levels. These findings emphasize the importance of strengthening adaptive coping strategies through psychological counseling and stress management training in higher education institutions, as a form of intervention that is expected to improve psychological well-being and build students' resilience in facing various life challenges.